Chaotification of Quasi-Zero Stiffness System via Direct Time-delay Feedback Control - Qing-chao Yang; Jing-jun Lou; Shu-yong Liu; Ai-min Diao (Universitas Ahmad Dahlan, 2013)
This paper presents a chaotification method based on direct time-delay feedback control for a quasi-zero-stiffness isolation system. An analytical function of time-delay feedback control is derived based on differential-geometry control theory. Furthermore, the feasibility and effectiveness of this method was verified by numerical simulations. Numerical simulations show that this method holds the favorable aspects including the advantage of using tiny control gain, the capability of chaotifying across a large range of parametric domain and the high feasibility of the control implement.